Acute pancreatitis in a child with sickle cell anemia - D., Manoj Kumar; Choppari, Komalatha; Thomas, Suresh R. J. (International Journal of Contemporary Pediatrics, 2020)
Sickle cell disease (SCD) is a term used for a group of genetic disorders characterized by production of Hb “S”. Sickle cell hemoglobin opathy occurs due to mutation of beta-globin gene situated on short arm of chromosome 11, where adenine is replaced by thymine in base of DNA coding for the amino acid in the sixth position in beta-globin chain. This leads to an amino acid change in beta chain of Hb molecule, from glutamic acid to valine. The result is profound change in the molecular stability and solubility of Hb “S”. Authors are reporting a 8-year-old girl who is a known case of sickle cell disease presented with complaints of intermittent pain abdomen and vomiting since 30 days. Investigations revealed elevated pancreatic enzymes with radiological evidence of pancreatitis. Packed red blood cell transfusion and appropriate supportive therapy given and child recovered well.